ANALISIS NILAI-NILAI KARAKTER PADA FILM ANIMASI UPIN DAN IPIN EPISODE MULANYA RAMADHAN DAN EPISODE IKHLAS DARI HATI - Shimfiyah Izaniyah; Ika Ratih Sulistiani; Mutiara Sari Dewi (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
Currently, children are very interested in electronic media, one of which is mass media, which affects behavior more than the cognitive aspects. The mass media that greatly influences children today is television to watch cartoon films, one of which is the animated film Upin and Ipin which are favored by children. The animated film Upin and Ipin tells about the world of children living their daily lives which can provide examples and instill character values for the audience, especially children. The character values contained in the animated film Upin and Ipin in the Beginning of Ramadan and Episode of Ikhlas dari Hati have found four of the five character values contained in Strengthening Character Education, namely the values of religious character, independence, mutual cooperation, and integrity. When children see shows that can educate and even teach good character, it cannot be denied that in the future they will become persons with character according to the expectations of the nation.Kata Kunci : Character Values, Upin and Ipin Animated Film